Characterization of viscosupplementation formulations using chemical exchange saturation transfer (ViscoCEST). Issue 1 (December 2016) - Haris, Mohammad; Singh, Anup; Reddy, Sanjana; Bagga, Puneet; Kneeland, J.; Tjoumakaris, Fotios; Hariharan, Hari; Marincola, Francesco; Reddy, Ravinder
Abstract Background Osteoarthritis (OA) is characterized by progressive loss of cartilage in joints, and is a major cause of pain and disability, and imposes significant health care expense. New therapies are being developed to treat the symptomatic effect of OA, one of which is intra-articular injection of viscosupplementations of different forms of hyaluronic acid (HA). The current study evaluates the chemical exchange saturation transfer (CEST) effect from two popular viscosupplementations [Hylan gf-20 (Synvisc) and hyaluronan (Orthovisc)] by targeting the exchangeable hydroxyl protons present on these molecules (ViscoCEST). Methods ViscoCEST imaging from two viscosupplementations (Synvisc and Orthovisc) was performed on a 7T Siemens whole body MRI scanner. ViscoCEST images were collected with different combination of saturation pulse power and saturation duration. Z spectra were acquired at B1rms of 3.6 μT and 1 s saturation duration by varying the frequency from −4 to +4 ppm in step size of 0.1 ppm. Field inhomogeneity (B0 ) and radiofrequency (B1 ) maps were also acquired to correct ViscoCEST contrast map for any inhomogeneity. Results Both viscosupplementations showed broad CEST effect (ViscoCEST), which peaked ~0.8 ppm from down field of water resonance. Orthovisc showed 20 % higher ViscoCEST contrast than Synvisc suggestive of more HA component in Orthovisc. Increased ViscoCEST contrast was observed from both viscosupplementations with increase in B1rms and saturation pulse duration. Conclusion ViscoCEST has a potential to image the spatial distribution of viscosupplements in vivo in patients' intra-articular space as well as temporal variation in their spatial distribution.